2002
DOI: 10.1007/s00429-002-0265-6
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic osteogenesis: two different types of bone formation

Abstract: The onset and development of intramembranous ossification centers in the cranial vault and around the shaft of long bones in five newborn rabbits and six chick embryos were studied by light (LM) and transmission electron microscopy (TEM). Two subsequent different types of bone formation were observed. We respectively named them static and dynamic osteogenesis, because the former is characterized by pluristratified cords of unexpectedly stationary osteoblasts, which differentiate at a fairly constant distance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
105
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(112 citation statements)
references
References 16 publications
7
105
0
Order By: Relevance
“…This zone was characterized by a large increase in bone formation rate during the first 17 days after the surgery up to a distance of 736 mm from the screw surface. This early peri-implant bone formation is in accordance with literature where it was shown to be the result of the so-called static osteogenesis [46,47]. Osteogenic cells and a new calcified matrix are therefore deposited after only a few days on the cement line created on the implant surface [48].…”
Section: Discussionsupporting
confidence: 88%
“…This zone was characterized by a large increase in bone formation rate during the first 17 days after the surgery up to a distance of 736 mm from the screw surface. This early peri-implant bone formation is in accordance with literature where it was shown to be the result of the so-called static osteogenesis [46,47]. Osteogenic cells and a new calcified matrix are therefore deposited after only a few days on the cement line created on the implant surface [48].…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have also demonstrated that regulation of vital reactions and consequent modeling and remodeling at the BIC interfaces might rapidly organize functional osseointegration to obtain a long-term stability of IPs for the occlusal rehabilitation therapy [8][9][10][11][12][13] . Previously, we have isolated and cultured mesenchyme cells (e.g., rat/human dental pulp cells, rat bone marrowderived stromal (BMS) cells, mouse KUSA/A (JCRB/ HSRRB; Osaka, Japan) cells), and elucidated that they were engineered to activate certain mechanisms to initiate hard tissue matrix deposition in both monolayer and 3-D cultures based on the guided bone regeneration (GBR) concept [14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…We have 3D-cultured JCRB1119:KUSA/A1 bone marrow-derived mesenchymal stem cell (MSC)s obtained from C3H/He mice (JCRB/HSRRB, Osaka, Japan) in a neutralised type I collagen gel (Cellmatrix Type I-A; Nitta Gelatin Inc., Osaka, Japan) with IPs, and observed hard tissue formation to mimic contact and the static osteogenesis in the GBR tissue surrounding titanium (Ti) IPs 2,9,[12][13][14][15][16][17][18][19] . Recently, we have investigated initial contact osteogenesis of HMS0014 MSCs (Yub621b, human bone-derived MSC line; Riken BRC, Tsukuba, Japan) on Ti discs (plates) subject to different surface modifications.…”
Section: Introductionmentioning
confidence: 99%